Analisis Faktor-Faktor Yang Mempengaruhi Keputusan Investasi Mahasiswa Akuntansi Di Kota Batam - Jesica; Haposan Banjarnahor (Komunitas Dosen Indonesia, 2023)
Accounting students in Batam City invest with the awareness of wanting to gain prosperity in the future by utilizing the remaining pocket money or residual salary in the hope that the investment made will generate a profit. The right investment decision is needed to achieve this goal. The purpose of this study was to determine the effect of financial literacy, herding and risk perception on investment decisions. Quantitative research methods based on primary data are used in this study. This study collected the necessary data by distributing questionnaires to several universities in Batam City with the main focus being accounting students, totaling 1,502 students. The Likert scale was used to measure the questionnaire using a sample of 316 respondents. The probability sampling technique is used in the sampling process. Statistical tools, namely the SPSS V26 program, are used to test or perform data analyses, namely: descriptive statistics, data quality tests, classical assumption tests, multiple linear regression tests, determinant coefficient tests, and hypothesis testing. The results of the study found that financial literacy, herding and risk perception had a positive and significant effect on the investment decisions of accounting students in Batam City